2020
DOI: 10.31579/2690-4861/006
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Dermoscopy In Umbilical Tumor

Abstract: The pelvic endometriosis is considered a relatively common, benign, estrogen-dependent disease associated with complaints of pelvic pain and infertility, affecting 6% to 10% of women of reproductive age. The etiopathogenesis of the disease is based on some theories and hypotheses. Classical theories include the hypothesis of migratory pathogenesis by retrograde menstrual flow, the theory of celomic metaplasia, the theory of embryonic rest or even iatrogenic deposition during abdominal surgical procedures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The systematic review revealed 10 papers reporting 10 cases of umbilical endometriosis [ 15 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In such cases, a clinical history indicating lesion evolution during the menstrual cycle may serve as an important diagnostic clue, however, this clinical sign was revealed in only 2 out of 10 included cases (20%) [ 15 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic review revealed 10 papers reporting 10 cases of umbilical endometriosis [ 15 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In such cases, a clinical history indicating lesion evolution during the menstrual cycle may serve as an important diagnostic clue, however, this clinical sign was revealed in only 2 out of 10 included cases (20%) [ 15 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Joanna Briggs Institute Appraisal tool questions; Table S2: Risk of bias assessment; Table S3: Overview of the characteristics of included studies. References [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] are cited in the Supplementary Materials.…”
mentioning
confidence: 99%